2015
DOI: 10.1186/s40249-015-0058-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Enterobius vermicularis infection in children in Gaozhou, Guangdong, China

Abstract: BackgroundEnterobius vermicularis infection is a prevalent intestinal parasitic disease in children. In this study, we explored the epidemiological status and risk factors for E. vermicularis infection in children in southern China.MethodsA cross-sectional survey was carried out in Gaozhou city, Guangdong province, China, in December 2011. Children aged 2–12 years from five schools participated in the study. The adhesive cellophane-tape perianal swab method was applied to detect E. vermicularis infection, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 19 publications
9
38
5
1
Order By: Relevance
“…Higher infection rates among boys may be due to boys involved in more activities, close contact with other children, and poor personal hygiene than girls. Among the age groups, children 3 to 6 years of age were more at risk to be infected with E. vermicularis, which is consistent with previous studies [13,29,30]. This could be because they have more group activities together, take naps together during the day on the oor mat, and poor personal hygiene than older children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Higher infection rates among boys may be due to boys involved in more activities, close contact with other children, and poor personal hygiene than girls. Among the age groups, children 3 to 6 years of age were more at risk to be infected with E. vermicularis, which is consistent with previous studies [13,29,30]. This could be because they have more group activities together, take naps together during the day on the oor mat, and poor personal hygiene than older children.…”
Section: Discussionsupporting
confidence: 88%
“…In many parts of the world, the prevalence of E. vermicularis infections varies between 0.21-54.86% [1][2][3][8][9][10][11][12][13][14][15][16][17]. In Thailand, the prevalence of E. vermicularis infections varies between 0-50.90% [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Enterobius vermicularis infection is favored by gaming habits and personal hygiene practices of children, as well as by bed-sharing and overcrowding. (29) As for the population studied, 50% lived in overcrowded conditions and shared single beds. Moreover, 47% of children had onychophagia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the proportions of infected and not infected children in particular study groups have remained similar over the years, with the highest prevalence of enterobiasis in children from orphanages (32.8 %) and signifi cantly lower in the group of children living in families (3.9 %). Despite the fact that the risk of enterobiasis increases in the older nursery and school children (over the age of 5 years) (Song et al, 2003;Remm 2006;Li et al, 2015), some researchers have not found a relationship between the age of children and the prevalence of E. vermicularis infection. In our study, similarly to the study results from Argentina (Pezzani et al, 2004), Estonia (Remm & Remm, 2008) and Norway (Bøås et al, 2012), the gender of children was unrelated with the enterobiasis prevalence, although several reports have shown boys to be more frequently affected than girls (Remm, 2006;Fig.…”
Section: Discussionmentioning
confidence: 99%